Exigências de proteína para o bagre-do-canal, Ictalurus punctatus, com base no desempenho produtivo, qualidade da carne, crescimento muscular e parâmetros sanguíneos - Schmitt, Tsiane Francielli (2015)
This work was accomplished in order to determine the crude protein requirements of the channel catfish, Ictalurus punctatus, in growing-finishing phase, based on growth performance, meat quality, muscle growth and blood parameters. The fish (N = 594; 66 ± 0,5 g) were distributed in 18 cages of 1000L, in a completely randomized design, with six treatments and three replicates (33 fish per cages); they were fed with extruded diets containing 24.36, 27.08, 29.50, 33, 09, 35.71 and 38.52% crude protein, twice daily until satiation. Fish fed diets containing graded levels of crude protein levels showed linear increase in final weight, weight gain and linear improvement in feed conversion. It was observed quadratic effect of protein levels on carcass yield, fillet yield and efficiency in nitrogen retention, where the highest values of these variables were estimated in fish fed 33.79; 33.88 and 31.24% crude protein levels, respectively. A linear increase in body crude protein contents in fish fed graded levels for crude protein diets was observed. A quadratic effect of dietary crude protein levels on visceral fat, body fat and fillets were observed, in which the lowest values of the variables were obtained in fish fed diets containing 33.35; 34.58 and 34.31% crude protein, respectively. The fish fed diet containing 33.09% protein showed reddish fillet compared to fish fed 24.36, 27.08 and 38.52% crude protein; and more yellowish fillet when compared to fish fed 27.08, 35.71 and 38.52%. The lowest fluid and water losses were observed in fillet of fish fed 29.50% crude protein, compared to fish fed 24.36% crude protein. The level of crude protein diet did not influence the frequency of occurrence of the fibers in different diameter classes. However, there was a gradual increase in cellular hypertrophy increased as from the level of 33.09%, the concentration of crude protein diet. No differences on hematological parameters occurred in fish fed graded levels of crude protein. The dietary level of 33.88% crude protein provides adequate growth performance with lower retention of body fat, high fillet yield and meat quality for the channel catfish.